Detection of Impurities in Bulk Drug and Capsule of Fluconazole - Yadav, A; Sharma, V.; Tripathi, S.; Soni, S. L. (Asian Journal of Pharmaceutical Research and Development, 2020)
Identification of impurities and their amounts in the fluconazole bulk drug and capsule FLUNACTM (150 mg) were done using HPLC with diode array detector. The composition of mobile phase was acetonitrile:water (85:15 %) with flow rate of 0.5 mL/min and detected at 260 ± 1 nm. Two impurities (one is known impurity A and other unknown impurity) were detected in the bulk drug and also in capsule FLUNAC (150 mg). The total amounts of impurities in fluconazole bulk drug and capsule were 0.368% and 0.392% respectively. In conclusion, the total amount of impurities was less than 1% which is acceptable.